Respuesta :

Answer:

a. [tex]y = -(x+1)^2+4[/tex]

b. [tex]y = \frac{1}{2} (x-2)^2-3[/tex]

Step-by-step explanation:

a. Vertex is (-1, 4)

so you get

[tex]y = a(x+1)^2+4[/tex]

plug in (1, 0) and get the a value

[tex]0 = a(1+1)^2+4\\0 = a*2^2 + 4\\0 = 4a + 4\\-4 = 4a\\a = -1[/tex]

final eq:

[tex]y = -(x+1)^2+4[/tex]

b. Vertex is (2, -3)

so you get

[tex]y = a(x-2)^2-3[/tex]

plug in (0, -1) and get the a value

[tex]-1 = a(0-2)^2-3\\-1 = a*(-2)^2 -3\\-1 = 4a -3\\2 = 4a\\a = \frac{1}{2}[/tex]

final eq:

[tex]y = \frac{1}{2} (x-2)^2-3[/tex]